The Relationship Between Gratitude and Resilience in Workers Who Experienced Layoffs Due to the Covid-19 Pandemic - Chintia Romadhon, Desti; Shafa Amadhea, Fyona; Septiana Maulania, Putri (International Journal of Social Science, Education, Communication and Economics, 2025)
This study aims to determine whether there is a relationship between gratitude and resilience in female workers who have been laid off due to the Covid-19 pandemic. The hypothesis in this study is that there is a relationship between gratitude and resilience. Participants in this study were 150 workers who were laid off due to the Covid-19 pandemic. Sampling was carried out using a purposive sampling technique. The measuring instrument used was a resilience scale that refers to the resilience aspect proposed by Connor and Davidson (2003) and a gratitude scale that refers to the gratitude aspect proposed by According to McCullough, Emmons and Tsang (2002). Hypothesis testing was carried out using Pearson's product moment correlation analysis. The results of the person's product moment correlation showed a value of r = 0.638 with a p value = 0.000 (p <0.05). This shows that there is a positive and significant relationship between gratitude and resilience. Thus the proposed hypothesis is accepted.